Comparative analysis of gender-oriented research - Zoirova, Aziza (Linguistics and Culture Review, 2021)
This article analyzes the research conducted by world scientists in the field of gender, identifying the relevance and necessity of the issues raised in them through scientific methods. In particular, scholars have studied the gender phenomenon, gender parameters, as well as the semantic grouping and gynocritical analysis generated through the gender component. A scientific approach to this work has been expressed. In the analysis of the research, it is substantiated by the fact that the issues in this area in Uzbek translation studies are not sufficiently studied.